The Concept of Forgiveness in Hannah Arendt’s Moral Theory: A Preliminary Study of Forgiveness in Political Theory and Political Conflict Resolution - Ngarmkham, Nathiya (Thai Journal of East Asian Studies, 2019)
Forgiveness is normally considered to be one of the significant moral concepts in Hannah Arendt’s ethical theory and political conflict resolution. She basically identifies it as a certain kind of action and signifies it as the only kind of activity that may possibly help redeem the predicament of irreversibility of action in political sphere. She also suggests that forgiveness is a moral principal which is different from others in general, because it is political within itself and it reconciles well to the political and public realm. This research paper aims at two purposes. Firstly, it aims to explain and interpret Arendt’s concept of forgiveness. In order to do so, it demonstrates the foundation of her arguments and examines their connections with her other concepts in political theory. The study forms its argument upon the concept of forgiveness found in The New Testament and The Old Testament. It also aims to study the concept of forgiveness used as a political conflict resolution in the public realm in general, especially in the concept of restorative justice. The research is conducted by documentary research method which employs conceptual analysis and hermeneutics methods. It has a final aim to provide a basic and theoretical knowledge about the concept of forgiveness, so it can be used as a grounding concept for the other studies in the field of political theory and political conflict resolution.